Efficacy of Platelet-rich Plasma for Low Back Pain: A Systematic Review and Meta-analysis - Xuan, Zhaopeng; Yu, Wenjun; Dou, Yichen; Wang, Tao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Platelet-rich plasma (PRP) may be beneficial for patients with low back pain. However, the results remain controversial. We conducted a systematic review and meta-analysis to explore the efficacy of PRP for low back pain.Methods PubMed, Embase, Web of Science, EBSCO, and Cochrane Library databases were searched systematically. Randomized controlled trials (RCTs) assessing the effect of PRP on low back pain were included. Two investigators independently searched articles, extracted data, and assessed the quality of included studies. The primary outcome was pain scores within 8 weeks. Meta-analysis was performed using the random-effects model.Results Three RCTs involving 131 patients were included in the meta-analysis. Overall, compared with control intervention for low back pain, PRP injection was found to reduce pain scores significantly (mean difference: − 1.47; 95% confidence interval [CI], − 2.12 to − 0.81; p < 0.0001), improve the number of patients with > 50% pain relief at 3 months (risk ratio [RR]: 4.14; 95% CI, 2.22–7.74; p < 0.00001), and offer relatively good patient satisfaction (RR: 1.91; 95% CI, 1.04–3.53; p = 0.04). No increase in adverse events was reported after PRP injection (RR: 1.92; 95% CI, 0.94-3.91; p = 0.07).Conclusions Compared with control intervention for low back pain, PRP injection was found to improve pain relief and patient satisfaction significantly with no increase in adverse events.
Keywords: low back pain; platelet-rich plasma; pain scores; systematic review; meta-analysis